2021
DOI: 10.1038/s41598-021-81511-1
|View full text |Cite
|
Sign up to set email alerts
|

Birth elicits a conserved neuroendocrine response with implications for perinatal osmoregulation and neuronal cell death

Abstract: Long-standing clinical findings report a dramatic surge of vasopressin in umbilical cord blood of the human neonate, but the neural underpinnings and function(s) of this phenomenon remain obscure. We studied neural activation in perinatal mice and rats, and found that birth triggers activation of the suprachiasmatic, supraoptic, and paraventricular nuclei of the hypothalamus. This was seen whether mice were born vaginally or via Cesarean section (C-section), and when birth timing was experimentally manipulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 89 publications
1
15
0
Order By: Relevance
“…Animal models support the findings of a perinatal surge in AVP and copeptin with higher levels in plasma after a vaginal than a Cesarean section (Hoffiz et al, 2021). In parallel to the increase in the peripheral blood circulation also central AVP mRNA levels and AVP protein levels rise significantly at birth (Spoljaric et al, 2017;Hoffiz et al, 2021). Hypoxic events, which in human fetuses accompany regularly uterine contractions before birth, have been identified in animal models as large driver of AVP and copeptin release into the peripheral blood circulation and in specific brain regions (L'Abate et al, 2013;Coldren et al, 2017;Summanen et al, 2018).…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Animal models support the findings of a perinatal surge in AVP and copeptin with higher levels in plasma after a vaginal than a Cesarean section (Hoffiz et al, 2021). In parallel to the increase in the peripheral blood circulation also central AVP mRNA levels and AVP protein levels rise significantly at birth (Spoljaric et al, 2017;Hoffiz et al, 2021). Hypoxic events, which in human fetuses accompany regularly uterine contractions before birth, have been identified in animal models as large driver of AVP and copeptin release into the peripheral blood circulation and in specific brain regions (L'Abate et al, 2013;Coldren et al, 2017;Summanen et al, 2018).…”
Section: Discussionsupporting
confidence: 61%
“…In fact, mild uterine contractions are sufficient to trigger fetal copeptin release (Wellmann et al, 2016) and a large multicenter randomized controlled trial is underway to study the clinical effect of mild uterine contractions prior to ECS on infants and mothers outcome after birth (Wellmann et al, 2021). Animal models support the findings of a perinatal surge in AVP and copeptin with higher levels in plasma after a vaginal than a Cesarean section (Hoffiz et al, 2021). In parallel to the increase in the peripheral blood circulation also central AVP mRNA levels and AVP protein levels rise significantly at birth (Spoljaric et al, 2017;Hoffiz et al, 2021).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…We also found that the expression of pro-inflammatory cytokines, especially interleukin 1β and tumor necrosis factor α, was markedly higher in the brains of mice born in the presence of a microbiota than in those born GF ( Castillo-Ruiz et al, 2018 ). More recently, we reported neural activation 3 h after birth in the PVN ( Hoffiz et al, 2021 ), a brain region that receives input from the vagus nerve and has a central role in immune regulation and the stress response. This timing coincides with the arrival of microbiota to the newborn gut, although we have yet to demonstrate that the two events are causally linked.…”
Section: How Does the Pioneer Microbiota Impact Brain Development?mentioning
confidence: 99%
“…The main stimulus for copeptin release at birth is represented by neuronal hypoxia due to transient cerebral hypoperfusion caused by maternal uterine contractions: as a consequence of this, naturally delivered infants exhibit up to 100-fold higher copeptin levels than children born by cesarean section, regardless of gestational age at birth [122]; moreover, the latter show higher copeptin levels and if affected by intra-uterine growth restriction or if the cesarean section was needed due to complications than elective, thus strengthening the role for copeptin as a stress biomarker [124][125][126]. Activation of the AVP system at birth is aimed at providing to the newborn natural analgesia, tuning neurobehavior in complex interactions between central and peripheral nervous systems and preventing excessive dehydration and weight loss in the first postnatal days [8]: a correlation between copeptin levels and all these phenomena has been recently highlighted in studies involving humans (after-birth nociception and osmoregulation) or animals (after-birth osmoregulation and neurobehavior) [127][128][129].…”
Section: Birth Stressmentioning
confidence: 99%